2006
DOI: 10.1083/jcb.200605037
|View full text |Cite
|
Sign up to set email alerts
|

MyoD-positive epiblast cells regulate skeletal muscle differentiation in the embryo

Abstract: MyoD mRNA is expressed in a subpopulation of cells within the embryonic epiblast. Most of these cells are incorporated into somites and synthesize Noggin. Ablation of MyoD-positive cells in the epiblast subsequently results in the herniation of organs through the ventral body wall, a decrease in the expression of Noggin, MyoD, Myf5, and myosin in the somites and limbs, and an increase in Pax-3–positive myogenic precursors. The addition of Noggin lateral to the somites compensates for the loss of MyoD-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
135
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(140 citation statements)
references
References 79 publications
5
135
0
Order By: Relevance
“…To determine whether G8 pos cells that responded to epithelial wound healing 24 or 72 h postinjury were indeed progeny of G8 pos cells present at T0, the fixed explants were labeled again with the G8 mAb (1:40), this time followed by an IgM secondary antibody conjugated to Alexa Fluor 488 (Invitrogen-Molecular Probes). Previous fate mapping studies in which G8 pos cells are tracked from the epiblast to embryonic tissues demonstrate that G8 mAb that tags G8 pos cells in the epiblast remains associated with these cells throughout the study and does not transfer to surrounding cells (16). A similar labeling protocol was used for the time-lapse studies, and images were acquired with a Coolsnap HQ camera (Photometrics) on a Nikon Eclipse microscope using Image-Pro Plus software (Phase 3 Imaging Systems).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine whether G8 pos cells that responded to epithelial wound healing 24 or 72 h postinjury were indeed progeny of G8 pos cells present at T0, the fixed explants were labeled again with the G8 mAb (1:40), this time followed by an IgM secondary antibody conjugated to Alexa Fluor 488 (Invitrogen-Molecular Probes). Previous fate mapping studies in which G8 pos cells are tracked from the epiblast to embryonic tissues demonstrate that G8 mAb that tags G8 pos cells in the epiblast remains associated with these cells throughout the study and does not transfer to surrounding cells (16). A similar labeling protocol was used for the time-lapse studies, and images were acquired with a Coolsnap HQ camera (Photometrics) on a Nikon Eclipse microscope using Image-Pro Plus software (Phase 3 Imaging Systems).…”
Section: Methodsmentioning
confidence: 99%
“…G8 pos cell ablation in epithelial explants followed a procedure previously described for ablation of G8 pos cells within the epiblast of the chicken embryo (16). For these studies, ex vivo lens epithelial explants were prepared in SFM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current model suggests that a combinatorial effect between the Wnt proteins and Shh is required for myogenesis (Borello et al, 2006;Cairns et al, 2008;Stern et al, 1995), whereas other studies present data showing that the Wnt proteins and Shh antagonize each other (Lee et al, 2000;Lee et al, 2001). Conversely, it was demonstrated that a combinatorial effect between the Wnt proteins and noggin is also sufficient for myogenesis (Reshef et al, 1998), and that noggin addition lateral to the somites can promote myogenesis even when MyoD-expressing cells are removed from the somite (Gerhart et al, 2006). Studies in the field agree that Bmp4 inhibits myogenesis (Hirsinger et al, 1997;Marcelle et al, 1997;Pourquie et al, 1996;Reshef et al, 1998;Sela-Donenfeld and Kalcheim, 2002;Watanabe and Le Douarin, 1996).…”
Section: Introductionmentioning
confidence: 88%